Prospek Pengembangan Potensi Wisata Kecamatan Tutur Kabupaten Pasuruan dalam Mendukung Pengelolaan Wisata di Wilayah Sekitar Gunung Bromo - Rebecha Prananta (Journal of Tourism and Creativity, 2019)
Abstract The area around Mount Bromo has many interesting tourism potential to be developed, such as eco-tourism, educational tourism, historical tourism, arts andculture and others. The government plans to make District Tutur, Pasuruan as a tourist destination will be related to the establishment of the Authority of BromoTengger Semeru. It is expected to be integrated, so that the TuturDistrictcan become part of the tourist destinations around Bromo. The method used in this research is descriptive method,using qualitative analysis. The approach used is a survey approach, observation and study of literature. Some tourist destinations are located in this area are: 1) Plantation Apples Krishna; 2) Bhakti Alam; 3) Condido Herbal Agro; 4) Mount Flora. The fourth potential of this tour has its own charm. With the fourth development potential of this tour, it is expected to support the development of local potential in the Tuturdistrict, Pasuruan in terms of tourism, so tourists who will visit Mount Bromo, would transit in the Tutur district and spend their money. Keywords: Tourism Destination;Mount Bromo;Tutur District; Descriptive Methods; Potensial Tourism Object.